Distributed Data Base - Rahmat Purnomo (Pt. Anagata Sembagi Education, 2024)
In the context of a distributed database, data is stored on various computers that are interconnected through communication media such as high-speed buses or telephone lines. A distributed database system consists of a set of sites, where each site has the ability to execute transactions that access data at one or more sites. A distributed database is a collection of logical data that is physically dispersed in a computer network, which is independent of current or future application programs. Fragmentation is a phenomenon in which storage space is inefficiently utilized, resulting in reduced storage capacity, while the term also refers to the condition of the deserted storage itself. Replication, on the other hand, is a technique for copying and distributing data and database objects from one database to another, as well as maintaining data consistency through synchronization between databases.